2015
DOI: 10.1016/j.combustflame.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and modeling study of propene oxidation. Part 2: Ignition delay time and flame speed measurements

Abstract: Experimental data obtained in this study (Part II) complement the speciation data presented in Part I, but also offer a basis for extensive facility cross-comparisons for both experimental ignition delay time (IDT) and laminar flame speed (LFS) observables.To improve understanding of the ignition characteristics of propene, a series IDT experiments were performed in six different shock tubes and two rapid compression machines (RCMs) under conditions not previously studied. This study is the first of its kind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
208
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(223 citation statements)
references
References 41 publications
12
208
0
Order By: Relevance
“…For the development and validation of combustion models, it is thus crucial to improve our knowledge of detailed C4 combustion chemistry. Building a comprehensive kinetic model for isobutene is also an extension of our work on propene [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the development and validation of combustion models, it is thus crucial to improve our knowledge of detailed C4 combustion chemistry. Building a comprehensive kinetic model for isobutene is also an extension of our work on propene [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Law and co-workers [15] reported laminar flame speeds and ignition temperatures for non-premixed counterflow flames at normal and elevated pressures. Their mechanism was built on previous studies by Zhang et al [16] and Cai et al [17] and included additional rate constants for the reactions of isobutene with Ḣ and Ö atoms and ȮH, HȮ 2 and ĊH 3 radicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One exception is Dataset 05 [66], where the deviation is greater. Further validation of the mechanisms used in this study can be found in [54][55][56][57][58].…”
Section: Comparison Of Fundamental Combustion Propertiesmentioning
confidence: 99%
“…For the reduction of the computation time, all hydrocarbon reactions greater than C 8 and greater than C 1 are removed in the C 8 -C 16 n-alkanes [55] and mechanisms AramcoMech 2.0 [56,57], respectively. The computation of the laminar flame speed for n-octane/air mixtures took around 60 CPU hours, while the computation of the other smaller fuels was much faster.…”
Section: Comparison Of Fundamental Combustion Propertiesmentioning
confidence: 99%